Meningkatkan Kemampuan Publikasi Ilmiah Kalangan Guru Sekolah Dasar - Krismanto, Wawan (DEDIKASI, 2018)
One form of mandatory activity for teachers in developing their competence is scientific publications.This is affirmed in Article 11 Peraturan Menteri PAN & RB No 16 tahun 2009 about Jabatan Fungsional Guru. Butin the field, there are still many teachers who have difficulty fulfilling the obligations of scientific publications sothat their careers are hampered. This also happened in the Kelompok Kerja Guru (KKG) XIV of Kota Parepare,specifically there were problems: 1) Limitations of understanding of scientific publications for the development ofprofessionalism and elementary school teacher careers, 2) Low competency in preparing applicative researchproposals for elementary school teachers, and 3) Low competency in the preparation of scientific articles andstrategies for publishing scientific articles in scientific journals. For this purpose, this service activity aims toprovide solutions to these problems, namely by implementing the Program Kemitraan Masyarakat (PKM) in theform of Research Assistance and Preparation of Scientific Articles Eligible Publication for Elementary Teachers.Activities are carried out in 3 stages: 1) debriefing material on Teacher Career Development Policy & itsRegulations, 2) Technical Guidance for Educational Research and 3) Technical Guidance for Preparing ScientificArticles that are Publication. After all stages of the PKM have been implemented, it can be concluded that theimplementation of this PKM has provided a solution to the partner's problems. Although individually not allteachers are able to achieve the target, in general the teachers of the KKG XIV Kota Parepare members have beenable to improve: 1) their insights on Teacher Career Development Policies & Regulations, 2) their ability totechnically plan and carry out educational research and 3) his ability to technically compile scientific articles that areworthy of publication.